2022
DOI: 10.7554/elife.77646
|View full text |Cite
|
Sign up to set email alerts
|

Mitotically heritable, RNA polymerase II-independent H3K4 dimethylation stimulates INO1 transcriptional memory

Abstract: For some inducible genes, the rate and molecular mechanism of transcriptional activation depends on the prior experiences of the cell. This phenomenon, called epigenetic transcriptional memory, accelerates reactivation and requires both changes in chromatin structure and recruitment of poised RNA Polymerase II (RNAPII) to the promoter. Memory of inositol starvation in budding yeast involves a positive feedback loop between transcription factor-dependent interaction with the nuclear pore complex and histone H3 … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
47
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 21 publications
(55 citation statements)
references
References 94 publications
(198 reference statements)
2
47
0
Order By: Relevance
“…Furthermore, these results suggest that while RNA polymerase II has been detected on promoters of primed HLA genes (Light et al 2013), it may itself not be the primary driver of transcriptional memory. In line with this, recent elegant experiments in yeast have shown that in the case of INO1 transcriptional memory, RNA polymerase II is poised but not required for memory (Sump et al 2022).…”
Section: Discussionmentioning
confidence: 75%
“…Furthermore, these results suggest that while RNA polymerase II has been detected on promoters of primed HLA genes (Light et al 2013), it may itself not be the primary driver of transcriptional memory. In line with this, recent elegant experiments in yeast have shown that in the case of INO1 transcriptional memory, RNA polymerase II is poised but not required for memory (Sump et al 2022).…”
Section: Discussionmentioning
confidence: 75%
“…In budding yeast, INO1 transcriptional memory induced by previous inositol starvation primes the rapid reactivation of INO1 upon exposure to the second stimulus ( D'Urso and Brickner, 2017 ). INO1 is required for the conversion of glucose to myoinositol in phospholipid biosynthesis ( Graves and Henry, 2000 ; Sump et al, 2022 ). The detailed molecular mechanism of INO1 memory is under investigation, and the current model of INO1 memory is summarized in a recent study ( Sump et al, 2022 ).…”
Section: Transcriptional Memory: Possible Contributor To Late-onset D...mentioning
confidence: 99%
“…INO1 is required for the conversion of glucose to myoinositol in phospholipid biosynthesis ( Graves and Henry, 2000 ; Sump et al, 2022 ). The detailed molecular mechanism of INO1 memory is under investigation, and the current model of INO1 memory is summarized in a recent study ( Sump et al, 2022 ). Briefly, INO1 memory requires a TF-dependent interaction with the nuclear pore complex (NPC), alterations in chromatin structure, and recruitment of “poised” Pol II to the promoter.…”
Section: Transcriptional Memory: Possible Contributor To Late-onset D...mentioning
confidence: 99%
See 2 more Smart Citations